Recent developments in Raman and infrared spectroscopy and imaging of bone tissue. Issue 2 (2004) - Morris Morris, Michael D. Michael D.; Finney Finney, William F. William F.
Abstract : Vibrational spectroscopy is an important tool in mineralized tissue research. This review focuses on recent applications of Raman and IR spectroscopies as contrast enhancement agents, tools for studying the chemical nature of changes in bone tissue with age and disease and understanding the molecular nature of changes in bone tissue during mechanical loading and fracture.